Anthony Ashley Cooper Shaftesbury: Three Stoic Exercises - Grzeliński, Adam (Folia Philosophica, 2021)
Three Stoic Exercises is the first Polish translation, done by Adam Grzeliński, of three excerpts from Shaftesbury’s notebooks: Character and Conduct, Attention and Relaxation, and Improvement being part included in the collection entitled Askêmata. These texts prove that these notebooks not only complement the contents of Characteristics of Men, Manners, Opinions, and Times, the three-volume set which made Shaftesbury a famous and influential philosopher, but they are to be seen mainly as a kind of moral exercises and soliloquies in which Shaftesbury comments the works of the stoics: Epictetus and Marcus Aurelius.